2022
DOI: 10.1017/wtc.2022.10
|View full text |Cite
|
Sign up to set email alerts
|

Toward a wearable monitor of local muscle fatigue during electrical muscle stimulation using tissue Doppler imaging

Abstract: Electrical muscle stimulation (EMS) is widely used in rehabilitation and athletic training to generate involuntary muscle contractions. However, EMS leads to rapid muscle fatigue, limiting the force a muscle can produce during prolonged use. Currently available methods to monitor localized muscle fatigue and recovery are generally not compatible with EMS. The purpose of this study was to examine whether Doppler ultrasound imaging can assess changes in stimulated muscle twitches that are related to muscle fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…SMG has advantages over sEMG, including spatial selectivity enabled by the depth resolution of US, as well as potentially superior SNR [58]. US can also be used to analyze muscle twitch response during functional electrical stimulation, which is not practical with sEMG [59]. New research has also shown the ability of US to isolate spatially-resolved motor unit action potentials [60].…”
Section: E Wearable Us For Rehabilitation Engineering and Neuroengine...mentioning
confidence: 99%
“…SMG has advantages over sEMG, including spatial selectivity enabled by the depth resolution of US, as well as potentially superior SNR [58]. US can also be used to analyze muscle twitch response during functional electrical stimulation, which is not practical with sEMG [59]. New research has also shown the ability of US to isolate spatially-resolved motor unit action potentials [60].…”
Section: E Wearable Us For Rehabilitation Engineering and Neuroengine...mentioning
confidence: 99%
“…[32,33,46] Another important consideration for any muscle sensing modality is muscle fatigue, a time-dependent phenomenon that affects both the amplitude and timing of force production, and often complicates the interpretation of measured signals. [47][48][49] The objective of this study was to correlate changes in surfacelevel muscle deformation with changes in volitionally-generated joint torque using a sensor-agnostic, high-resolution, and noncontact approach. A 2D laser profilometer was used to capture a high-resolution line profile of the skin's surface, measuring micron-scale changes in height relative to the laser head by scanning over a fixed distance and providing detailed height data.…”
Section: Introductionmentioning
confidence: 99%